Black African Students in Predominantly White U.S. Higher Education Institutions: Drivers Influencing Their Identification and Commitment - Yaro, Ibrahima Fatin; Mize Smith, Jennifer (Journal of International Students, 2024)
Black African students are increasingly choosing the United States as their preferred destination for higher education, and many choose to study at predominantly White institutions. The purpose of this qualitative study was to investigate factors that may influence their identification and commitment to those institutions. Researchers interviewed 20 sub-Saharan Africans at a predominantly White Southeastern university. Findings revealed that construed external image, overall satisfaction with the school, promotion of the institution, and willingness to maintain membership shape the extent to which Black African students are identified and committed to their university of choice. Furthermore, the study also found that prestige does not appear to influence Sub-Saharan African students’ identification and commitment to a school in the U.S., but race has mixed effects depending on how it gets interpreted by students. These findings suggest implications for research and practice for student affairs professionals to better serve and retain their international populations.